Fuel wood burning and its effect on the environment with Reference to tribal villages of Bolangir, Orissa, India - Sarada Prasad Mohapatra (Journal of Research in Biology, 2011)
Studies on air pollution due to burning of fuel wood for cooking purpose is alarming day by day in the tribal villages of Bolangir Dist. of Orissa. About 85 household are selected for the study, which burn about 254 tonnes of fuel wood annually. A negative correlation exists between annual income and fire wood consumption of household. Due to heavy use of firewood the health status of women and children are degrading day by day and they are more vulnerable to serious diseases like asthma, skin cancer and other respiratory diseases.